(untitled) (Interdisciplinary Studies Journal, 2024)
The present study aims to investigate what inmates of a penitentiary system think about the practice of physical activity, specifically sports, seeking to evaluate the impacts of the practice of Physical Education from the inmates’ point of view. The research in question investigated the impact of Education Physics, specifically sports practice, in the process of resocialization of inmates in a male Provisional Detention Center (CDP) in the State of Espírito Santo. Thus, the lack of effectiveness of the prison system in meeting legal objectives is highlighted as a challenge, highlighting the need for alternatives, with Physical Education emerging as a possible solution. The research was conducted over three months, equivalent to one academic semester, with 37 participants. The analysis sought to understand inmates’ perceptions about the practice of physical activity, especially in the prison environment. Thus, the results reveal a positive view of sports practice by inmates, highlighting physical, emotional and social benefits. The relationship between physical activity and the reduction of violence and conflicts within prison is evident. Suggestions from inmates to improve sports include diversifying activities, improving infrastructure and access to appropriate equipment. The study contributes significantly to the understanding of the transformative role of Physical Education in the prison environment and highlights the importance of humanized approaches adapted to the needs of inmates.